Precursor glass, glass ceramic, chemically strengthened glass ceramic and glass preparation method
By using low-temperature crystallization treatment and precursor glass with specific component design, the problem of impurity phase generation in the production of glass-ceramics has been solved, achieving high crystallinity and excellent optical and mechanical properties, and improving drop resistance.
Patent Information
- Application Number
- CN202510629144.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-10-17
AI Technical Summary
Existing technologies struggle to effectively remove impurity phases in the production of glass-ceramics, leading to damage to optical and mechanical properties. Furthermore, traditional heat treatment processes cannot simultaneously achieve high crystallinity and low impurity phase formation.
By using precursor glass suitable for low-temperature crystallization, and through the design of specific components and relationships, the ionic activity of the glass and the thermal kinetic energy of oxide molecules are controlled to achieve high crystallinity and low impurity phase formation at low temperatures. Chemically strengthened microcrystalline glass is then prepared by combining heat treatment and ion exchange treatment.
It improves the optical and mechanical properties of glass-ceramics, ensuring high crystallinity while effectively controlling the formation of impurity phases, and enhancing the glass's drop resistance and mechanical strength.
Smart Images

Figure CN120794348A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of materials, in particular to the technical field of microcrystalline glass. Specifically, the present application discloses a precursor glass, a microcrystalline glass, a chemically strengthened microcrystalline glass and a glass preparation method. BACKGROUND
[0002] Microcrystalline glass has tiny crystals inside. The tiny crystals themselves have high strength, and can hinder crack propagation when the glass is impacted to produce cracks, so that the microcrystalline glass has stronger mechanical properties than ordinary glass and performs well in drop resistance tests. Microcrystalline glass has developed rapidly since this century, and in recent years, microcrystalline glass used for mobile phone covers has developed particularly rapidly. Due to the high strength and drop resistance of microcrystalline glass, it is deeply welcomed by the consumer electronics market.
[0003] In the production process of microcrystalline glass, the precursor glass generally needs to have a strong crystallization tendency to ensure uniform crystallization of the whole glass, which leads to the easy generation of some impurities such as lithium metasilicate and spodumene. These impurities have different degrees of damage to the mechanical and optical properties of microcrystalline glass, but they are difficult to remove in actual production. These impurities can be generated in the glass melting, heat treatment process and strengthening process. The main reason is that the crystal structure of these impurities is closely related to the structure of glass and microcrystalline glass, such as high-temperature phase transition and similar structure, which is difficult to completely exclude. At present, in the related technology, a relatively mild heat treatment process (shorter heat treatment time and / or lower heat treatment temperature) is generally used to reduce the generation of impurities, that is, to obtain a relatively pure target crystal phase by sacrificing crystallinity, but the optical and mechanical properties of the microcrystalline glass cannot be effectively guaranteed.
[0004] It should be noted that the technology described in this section is not necessarily the technology that has been previously conceived or used. Unless otherwise indicated, nothing in this section should be assumed to be prior art merely because of its inclusion in this section. Similarly, issues mentioned in this section should not be assumed to have been admitted to be prior art unless otherwise indicated. SUMMARY
[0005] The present application provides a precursor glass, a microcrystalline glass, a chemically strengthened microcrystalline glass and a glass preparation method, aiming to at least solve one of the problems in the related art to some extent.
[0006] The first aspect of the present application provides a precursor glass suitable for low-temperature crystallization treatment, which satisfies the following relationship:
[0007] δ=a*n RO +b*(n Na2O +n K2O )+c*nLi2O ,
[0008] η=12.5 / (0.55+4.61*i^0.57),
[0009] 0.25≤δ / η≤0.6;
[0010] Among them, δ represents the ionic activity of each ion in the glass, η represents the correlation index between the kinetic energy of thermal motion of oxide molecules in the glass and the characteristic temperature point, n represents the molar percentage content of each oxide, and i is the characteristic temperature coefficient, 1.3<A<1.9, 1.3<B<2.3, 1.2<C<1.8, 5.96<i<10.13.
[0011] Optionally, the precursor glass further satisfies the following relationship:
[0012] ε=A*n SiO2 +B*n B2O3 +C*n Al2O3 +D*n P2O5 +E*n RO +F*n R2O ,
[0013] 22≤ε≤24.8;
[0014] Among them, ε represents the degree of atomic stacking, n represents the molar percentage content of each oxide, A, B, C, D, E, and F are constants, A = 26.1 to 28.3, B = 18.3 to 27.3, C = 40.2 to 42.7, D = 56.1 to 63.7, E = 12.2 to 22.6, and F = 10.9 to 36.2.
[0015] Optionally, the precursor glass further satisfies the following relationship:
[0016] ε=A*n SiO2 +B*n b2o3 +C*n Al2O3 +D*n P2O5 +12.5*n MgO +14.4*
[0017] n CaO +11.2*n Li2O +20.2*n Na2O +34*n K2O , 22.5≤ε≤24.1.
[0018] Optionally, the precursor glass comprises, in mole percentage, the following components:
[0019] SiO2 greater than or equal to 60% and less than or equal to 78%;
[0020] Al2O3 greater than or equal to 1.5% and less than or equal to 6.7%;
[0021] Li2O greater than or equal to 16% and less than or equal to 26.8%;
[0022] Na2O greater than or equal to 0 and less than or equal to 6.5%;
[0023] K2O greater than or equal to 0 and less than or equal to 4%;
[0024] P2O5 greater than or equal to 0.3% and less than or equal to 2.5%;
[0025] ZrO2 greater than or equal to 0 and less than or equal to 5%;
[0026] RO greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, BaO;
[0027] a fining agent greater than or equal to 0 and less than or equal to 1%.
[0028] Optionally, the precursor glass, in mole percent, further comprises: B2O3 greater than or equal to 0 and less than or equal to 4.8%; and / or, TiO2 greater than or equal to 0% and less than or equal to 4%; and / or, Y2O3 greater than or equal to 0 and less than or equal to 4%; and / or, La2O3 greater than or equal to 0 and less than or equal to 0.5%.
[0029] Optionally, the precursor glass, in mole percent, comprises: Al2O3 greater than or equal to 1.5% and less than or equal to 5.5%; or, Al2O3 greater than or equal to 2% and less than or equal to 6.7%.
[0030] Optionally, the precursor glass, in mole percent, comprises: Al2O3 greater than or equal to 2% and less than or equal to 4.2%; or, Al2O3 greater than or equal to 3.5% and less than or equal to 5.2%.
[0031] Optionally, the precursor glass, in mole percent, comprises: P2O5 greater than or equal to 0 and less than or equal to 2.2%.
[0032] Optionally, the precursor glass, in mole percent, comprises: Li2O greater than or equal to 18% and less than or equal to 26.8%, Na2O greater than or equal to 0 and less than or equal to 6.5%, K2O greater than or equal to 0 and less than or equal to 4%.
[0033] Optionally, the precursor glass includes, in mole percent, Li2O greater than or equal to 22.2% and less than or equal to 25.8%, Na2O greater than or equal to 0 and less than or equal to 3.1%, and K2O greater than or equal to 0 and less than or equal to 1.2%.
[0034] Optionally, the precursor glass includes, in mole percent, Li2O greater than or equal to 16% and less than or equal to 24%, Na2O greater than or equal to 0 and less than or equal to 5%, and K2O greater than or equal to 0 and less than or equal to 4%.
[0035] Optionally, the precursor glass includes, in mole percent, Li2O greater than or equal to 20.5% and less than or equal to 23.5%, Na2O greater than or equal to 0 and less than or equal to 2%, and K2O greater than or equal to 0 and less than or equal to 0.5%.
[0036] Optionally, the precursor glass further includes at least one of Nb2O5, Ta2O5, HfO2, and Bi2O3.
[0037] Optionally, the precursor glass includes, in mole percent, at least one of the following relationships:
[0038] 5 ≤ n Li2O / (n Na2O +n K2O ) ≤ 15;
[0039] 7 ≤ n Li2O / (n CaO +n MgO +n ZnO ) ≤ 18;
[0040] 0.25 ≤ n Li2O / (n SiO2 +n Al2O3 ) ≤ 0.5;
[0041] Li2O, Na2O, and K2O are all alkali metal oxides. By adding alkali metal oxides in combination, a mixed alkali effect can be formed, which can improve the crosslinking density of the glass network, chemical stability and other properties, and significantly improve the stability of micro-glass products. Li2O / (Na2O+K2O) needs to meet a certain value range. If the ratio of (Na2O+K2O) is too low, the mixed alkali effect cannot be formed. If the ratio of (Na2O+K2O) is too high, it will affect the formation ratio and formation speed of lithium crystals in the glass; (CaO+MgO+ZnO) has a higher field strength, It can enhance the mechanical properties of glass, such as elastic modulus and Vickers hardness. If the ratio of (CaO+MgO+ZnO) is too low, the beneficial effect of enhancing the mechanical properties cannot be achieved. If it is too high, it will promote the malignant growth of crystals and make it difficult to form microcrystals. (SiO2+Al2O3) is the main network former in glass, which plays a decisive role in the viscosity of glass and the network crosslinking density. If the ratio of (SiO2+Al2O3) is too low, controllable crystallization cannot be formed under suitable viscosity and temperature conditions. If the ratio is too high, it will affect the crystallinity and crystal size of the glass, and at the same time make the glass viscosity too high, which is not conducive to production.
[0042] A second aspect of the present application provides a glass-ceramic, which is obtained by heat treating the precursor glass described in the first aspect.
[0043] Optionally, the lower limit crystallization temperature of the glass-ceramics is 553-639°C, and the upper limit crystallization temperature is 989-1123°C.
[0044] Optionally, the crystalline phase of the microcrystalline glass includes lithium disilicate and petalite, the average grain size of the lithium disilicate is less than or equal to 32.5-39.3 nm, the average grain size of the petalite is less than or equal to 24.6-29.1 nm, and the crystallinity is greater than or equal to 84.72%.
[0045] Optionally, the lithium disilicate crystalline phase meets the following indicators: the size of 98% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 55 nm, the size of 95% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 50 nm, and the size of 80% of the grains in the lithium disilicate crystalline phase as a whole is less than or equal to 45 nm; the petalite crystalline phase meets the following indicators: the size of 98% of the grains in the petalite crystalline phase as a whole is less than or equal to 45 nm, the size of 95% of the grains in the petalite crystalline phase as a whole is less than or equal to 40 nm, and the size of 80% of the grains in the petalite crystalline phase as a whole is less than or equal to 30 nm; the crystallinity is greater than or equal to 85.8%.
[0046] Optionally, the glass-ceramics meets at least one of the following performance indicators: Vickers hardness greater than or equal to 727 kgf / mm 2a Young's modulus greater than or equal to 78.3 GPa, a shear modulus greater than or equal to 33.27 GPa, a |B| value less than or equal to 0.77% when the thickness is 0.55 mm, a haze less than or equal to 0.15%, and a transmittance greater than or equal to 91% relative to visible light with a wavelength of 550 nm. 1 / 2 a Young's modulus greater than or equal to 78.3 GPa, a shear modulus greater than or equal to 33.27 GPa, a |B| value less than or equal to 0.77% when the thickness is 0.55 mm, a haze less than or equal to 0.15%, and a transmittance greater than or equal to 91% relative to visible light with a wavelength of 550 nm.
[0047] The third aspect of the present application provides a chemically strengthened microcrystalline glass, which is obtained by sequentially subjecting the precursor glass according to the first aspect to heat treatment and ion exchange treatment.
[0048] Optionally, the chemically strengthened microcrystalline glass satisfies at least one of the following performance indexes: a Vickers hardness greater than or equal to 655 kgf / mm 2 a fracture toughness greater than or equal to 1.2 Mpa·m 1 / 2 a Young's modulus greater than or equal to 98.38 GPa, a shear modulus greater than or equal to 39.35 GPa, a |B| value less than or equal to 0.77% when the thickness is 0.55 mm, a haze less than or equal to 0.13%, a transmittance greater than or equal to 91% relative to visible light with a wavelength of 550 nm, a nine-point ball drop test height based on a 32 g steel ball of 980-1290 mm when the thickness is 0.55 mm, a maximum bending strength of 1052-1200 MPa, a whole machine drop test height based on 80 mesh sandpaper of 850-1020 mm, and a whole machine drop test height based on 180 mesh sandpaper of 1200-1600 mm.
[0049] The fourth aspect of the present application provides a glass preparation method, comprising:
[0050] mixing raw materials according to a glass formula, melting the raw materials at a preset melting temperature and for a preset melting time, and obtaining a precursor glass after forming and annealing;
[0051] subjecting the precursor glass to heat treatment to obtain a microcrystalline glass;
[0052] wherein the precursor glass satisfies the following relationship:
[0053] δ=a*n RO +b*(n Na2O +n K2O )+c*n Li2O ,
[0054] η=12.5 / (0.55+4.61*i^0.57),
[0055] 0.25≤δ / η≤0.6;
[0056] Wherein, δ represents the ion activity degree of each ion in the glass, η represents the correlation index of the kinetic energy of the thermal motion of the oxide molecules in the glass and the characteristic temperature point, n represents the corresponding molar percentage content of each oxide, i is the characteristic temperature coefficient, 1.3 < a < 1.9, 1.3 < b < 2.3, 1.2 < c < 1.8, and 5.96 < i < 10.13.
[0057] Optionally, the heat treatment of the precursor glass comprises: placing the precursor glass in a crystallization furnace, heating to 500-610 ℃ at a heating rate greater than or equal to 6 ℃ / min and then holding for 200-300 min, then heating to 655-800 ℃ at a heating rate greater than or equal to 6 ℃ / min and then holding for 60-120 min, and finally cooling at a cooling rate less than or equal to 2 ℃ / min.
[0058] Optionally, the heat treatment of the precursor glass comprises: placing the precursor glass in a crystallization furnace, heating to 560-590 ℃ at a heating rate of 8-12 ℃ / min and then holding for 220-250 min, then heating to 750-790 ℃ at a heating rate of 8-12 ℃ / min and then holding for 70-90 min, and finally cooling at a cooling rate less than or equal to 2 ℃ / min.
[0059] Optionally, the glass preparation method further comprises: subjecting the microcrystalline glass to a heat bending treatment through a heat bending work station; wherein the pressure of the heat bending work station is 0.7-1.1 MPa, and the operation time of a single work station is 70-110 s.
[0060] Optionally, the heat bending treatment needs to pass through four preheating work stations, three hot pressing work stations, and two cooling work stations; wherein the operation temperature of the first preheating work station is 430-470 ℃, the operation temperature of the second preheating work station is 530-570 ℃, the operation temperature of the third preheating work station is 630-670 ℃, the operation temperature of the fourth preheating work station is 710-730 ℃, the operation temperature of the first hot pressing work station is 740-760 ℃, the operation temperature of the second hot pressing work station is 740-760 ℃, the operation temperature of the third hot pressing work station is 580-620 ℃, the operation temperature of the first cooling work station is 430-470 ℃, and the operation temperature of the second cooling work station is 280-320 ℃.
[0061] Optionally, the glass preparation method further comprises: immersing the glass-ceramics into a chemical strengthening salt bath for ion exchange treatment to obtain the chemical strengthening glass-ceramics; wherein the chemical strengthening salt bath comprises, in percentage by mass: greater than or equal to 9.99% and less than or equal to 39.99% of KNO3, greater than or equal to 59.99% and less than or equal to 89.99% of NaNO3, greater than or equal to 0.03% and less than or equal to 0.1% of LiNO3.
[0062] Optionally, the temperature of the chemical strengthening salt bath is 460-490 ℃, and the ion exchange treatment is performed for 4-10 hours.
[0063] As can be seen from the above, according to the precursor glass, glass-ceramics, chemical strengthening glass-ceramics and glass preparation method provided by the scheme, the precursor glass satisfies the following relationship: δ = a * n RO +b * (n Na2O +n K2O )+c * n Li2O ), η = 12.5 / (0.55 + 4.61 * i ^ 0.57), 0.25 ≤ δ / η ≤ 0.6; wherein δ represents the ion activity degree of each ion in the glass, η represents the correlation index of the kinetic energy of oxide molecule thermal motion in the glass and the characteristic temperature point, n represents the corresponding molar percentage content of each oxide, a, b and c are constants, i is a characteristic temperature coefficient, 1.3 < a < 1.9, 1.3 < b < 2.3, 1.2 < c < 1.8, and 5.96 < i < 10.13. Since alkali metals and alkaline earth metals have a significant effect on increasing the glass crystallization tendency, Na2O and K2O have a prominent effect on increasing the glass crystallization tendency. This is because their ionic radii are small and they are more easily attracted by high field strength ions under suitable temperature conditions. By introducing the δ calculation formula, the different acting oxides in the glass can be classified and calculated, and the different factors affecting the crystallization tendency can be comprehensively evaluated, so as to describe the relationship between the electric field strength of different oxides in the glass and ion migration. By introducing the η calculation formula, the relationship between the kinetic energy of oxide molecule thermal motion in the glass and the characteristic temperature point is related to the above crystallization strength, and the crystallization tendency of crystallization at a lower temperature is comprehensively evaluated.
[0064] Further, the crystallization tendency of the glass is characterized by describing the ion activity degree of the glass by δ / η, and the value of δ / η is set in a specific range, so that the glass viscosity is suitable for low-temperature crystallization. It is worth mentioning that the low-temperature crystallization mentioned in the embodiment refers to the crystallization temperature required in the embodiment of the application is lower than the hot forming and hot working temperature, but still can ensure high crystallinity. Since the crystallization temperature is relatively low, the generation of impurities can be effectively controlled. The value range of the application is optimized and designed, so that the glass viscosity is suitable for low-temperature crystallization, and the crystallinity of the target crystal phase and the control of impurities are considered, and the optical and mechanical properties of the glass are improved.
[0065] It should be understood that the content described in this part is not intended to identify the key or important features of the application, nor is it used to limit the scope of the application. The further effects of the above-mentioned non-conventional optional modes will be described in conjunction with the specific embodiments below. BRIEF DESCRIPTION OF DRAWINGS
[0066] The accompanying drawings, which are included to provide a further understanding of the application and are incorporated in and constitute a part of this specification, illustrate embodiments of the application and together with the description serve to explain exemplary embodiments of the application. The drawings presented are for exemplary purposes only and do not limit the scope of the claims. In all the drawings, the same reference signs refer to similar but not necessarily identical elements.
[0067] Figure 1 DSC test curve of the microcrystalline glass corresponding to embodiment 4 provided in the application;
[0068] Figure 2 XRD test curve of the microcrystalline glass corresponding to embodiment 4 provided in the application;
[0069] Figure 3 Scanning electron microscope image of the microcrystalline glass corresponding to embodiment 4 provided in the application;
[0070] Figure 4 Viscosity-temperature curve of the microcrystalline glass corresponding to embodiment 4 provided in the application. DETAILED DESCRIPTION
[0071] In order to make the purposes, features and advantages of the application more obvious and easy to understand, the technical solutions in the embodiments of the application will be described clearly and completely in conjunction with the drawings in the embodiments of the application. Obviously, the described embodiments are only a part of the embodiments of the application, not all the embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the application.
[0072] In the description of the embodiments of the present application, the term "a plurality of" means two or more, unless otherwise explicitly specified; the term "comprising" indicates the presence of described features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof; the term "and / or" describes the association relationship of associated objects, and means that there can be three relationships, for example, A and / or B can include the three cases of A alone, A and B together, and B alone, the character " / " generally means that the associated objects before and after the " / " have an "or" relationship; the term "about" means that the content, size, parameter, etc. is not and need not be accurate, and can be approximate or higher, lower, in general, whether or not explicitly stated, the content, size, parameter, etc. should be "about" or "approximate"; the terms "preferably", "optionally" do not limit the scope of the present application, nor do they mean that certain technical features are critical or essential to the embodiments of the present application, but it should be understood that they are only indicative of certain aspects of the embodiments of the present application.
[0073] Unless specifically indicated in a particular case, the numerical ranges recited in the embodiments of the present application are intended to include the end points of the numerical ranges and all integers and fractions within the ranges. When a certain amount, solubility or other parameter is described in the form of a preferred range or a preferred value, it should be understood that any range combining any preferred range with a preferred range, a preferred value with a preferred value, a preferred range with a preferred value is disclosed, regardless of whether such two-by-two combination is specifically explained in the embodiments.
[0074] Unless specifically indicated in a particular case, the component content recited in the embodiments of the present application is expressed in terms of mole percent mol%.
[0075] Term explanation
[0076] Precursor glass: refers to a glass that has not been subjected to nucleation treatment, crystallization treatment and strengthening treatment.
[0077] Microcrystalline glass: also known as glass ceramic, is a kind of solid composite material containing glass phase and microcrystalline phase prepared by targeted controlled heat treatment of precursor glass. The microcrystalline phase here is also called crystalline phase, crystalline phase, crystalline phase in other materials.
[0078] Chemically strengthened glass-ceramics: refers to the solid composite material obtained after the glass-ceramics is subjected to chemical strengthening treatment. It should be understood that when subjected to high-temperature chemical strengthening treatment or high-temperature ion exchange process treatment, alkali metal ions with large ionic radius (such as potassium ions, sodium ions) in the salt bath or molten salt (molten salt) will replace alkali metal ions with small ionic radius (such as sodium ions, lithium ions) in the glass-ceramics, thereby generating an exchange ion volume difference, generating a high-to-low compressive stress from the surface to the inside of the surface layer of the glass-ceramics, hindering and delaying the expansion of micro-cracks, and achieving the purpose of improving the mechanical strength of the glass-ceramics.
[0079] Nucleation temperature: refers to the temperature at which crystal nuclei are formed.
[0080] Crystallization temperature: refers to the temperature at which the target crystal growth rate is controllable.
[0081] Transmittance: the intensity of the light transmitted through the glass surface is the ratio of the intensity of the incident light.
[0082] In the present application, the average transmittance of the glass-ceramics in the visible light range refers to the average value of the transmittance measured at wavelengths of 360nm-740nm. The average transmittance of the glass-ceramics in the wavelength range of 360nm-740nm is measured using a Konica Minolta Spectrophotometer CM-3600A.
[0083] Crystallinity: refers to the percentage of the total mass of the crystalline phase / crystal in the glass-ceramics.
[0084] Haze (Haze(C)): refers to the percentage of the transmitted light intensity deviating from the incident light by more than 2.5°. The haze value in the present application is measured using a Konica Minolta Spectrophotometer CM-3600A under standard C light source.
[0085] L value: the L value in the present application is the specular reflectance (SCI) L value, which represents the brightness of the material. A positive L value indicates a white bias, and a negative L value indicates a black bias.
[0086] a value: the a value in the present application is the specular reflectance (SCI) a value, which represents the red-green value of the material. A positive a value indicates a red bias, and a negative a value indicates a green bias.
[0087] b value: the b value in the present application is the specular reflectance (SCI) b value, which represents the yellow-blue value of the material. A positive b value indicates a yellow bias, and a negative b value indicates a blue bias.
[0088] In the present invention, Vickers hardness refers to a standard for indicating the hardness of a material proposed by Robert L. Smith and George E. Sandland in 1921 at Vickers Ltd.
[0089] In the present invention, fracture toughness refers to the resistance value exhibited by a material when a crack or crack-like defect in a sample or member occurs as a starting point and no longer rapidly breaks with an increase in load, i.e., when so-called unstable fracture occurs.
[0090] In the present invention, CS_50 refers to the compressive stress value at a depth of 50 μm from the surface of the glass.
[0091] In the present invention, |CT_CV| refers to the absolute value of the maximum value of the tensile stress, specifically the absolute value of the maximum value of all tensile stresses in the tensile stress layer.
[0092] In the present invention, |CT_AV| refers to the absolute value of the average tensile stress in the tensile stress layer, specifically the absolute value of the average value of all tensile stresses in the tensile stress layer.
[0093] In the present invention, DOL_0 refers to the depth of the compressive stress layer, also referred to as the compressive stress layer depth, and refers to the distance from any surface of the glass to the position where the compressive stress near the surface is zero.
[0094] In a first aspect, the present invention provides a strengthened microcrystalline glass having excellent drop resistance performance, with the following crystallization properties and stress properties.
[0095] In general, drop impact is a puncture-type failure, and under impact, sharp particles easily break through the glass surface CS, causing a 30-50 μm deep pit, and then forming a crack extension at the pit, breaking through the compressive stress region, thereby breaking the glass. CS_50 indicates the magnitude of the compressive stress at a depth of 50 μm, and the greater the stress at this point, the more conducive to inhibiting the formation of cracks at the pit. A deeper DOL-0 represents a larger region that hinders crack extension, and CT-CV is the highest point of the tensile stress, and CT-AV is the average value of the tensile stress, which indirectly indicates the magnitude of the deep compressive stress. The more superior the stress performance, the more difficult it is for cracks to expand.
[0096] Drop test: The glass sheet was adhered to a counterweight steel sheet to simulate the drop of the entire machine, and the counterweight steel sheet weighed 200 g.
[0097] The above substrate glass is heat treated in a resistance furnace, and the microcrystalline glass sample bricks for chemical strengthening are obtained after the heat treatment process (nucleation temperature / nucleation time, crystallization temperature / nucleation time, and heating rate during the heat treatment process). The mirror-smooth microcrystalline glass sheet is obtained after cutting, CNC processing (computer numerical control), and polishing of the microcrystalline glass sample bricks.
[0098] The physical property parameters of the prepared microcrystalline glass are tested according to the following method:
[0099] Crystallization upper limit and crystallization lower limit: The test is performed using an Orton GTF-MD-16 gradient furnace. The glass strip is placed on the ceramic tube of the Orton gradient furnace, and the heating parameters are set. After the furnace is cooled, the sample is taken out, and the corresponding position is recorded. Since one end of the sample is low in temperature and the other end is high in temperature, the temperature can be accurately judged, and the standard ASTM E 228-17 is referred to.
[0100] Vickers hardness test: A diamond Vickers indenter is pressed into the surface of the sample under a load of 1.916N-49.03N to form an indentation. The load is divided by the value calculated from the average diagonal length of the indentation to obtain the indentation surface area, and the standard GBT 37900-2019 is referred to.
[0101] Fracture toughness test: A diamond Vickers indenter is pressed into the surface of the sample under a load of 1.916N-49.03N to form an indentation, and pre-cracks are generated at the four corners of the indentation. The value calculated from the load and the crack propagation length of the indentation is calculated, and the standard GBT 37900-2019 is referred to.
[0102] Young's modulus test: The Young's modulus of the sample is obtained by acoustic wave testing. The instrument is UMS-100 ultrasonic material characterization system, and the standard GBT 37780-2019 is referred to.
[0103] XRD test: The microcrystalline glass sheet is ground into fine glass powder with a particle size of less than 75μm, and then tested by X-ray diffractometer (Shimadzu XRD-6100) to obtain the XRD diffraction peak curve. The X-ray diffractometer used in the present application is Shimadzu XRD-6100, the target material is copper, the test incident angle range is 2θ=10-80°, the scanning speed is 0.2° / min, the working voltage is 40kV, and the working current is 30mA. The crystal phase of the sample is obtained by analyzing the XRD diffraction data using JADE software.
[0104] Average grain size: the average grain size of the sample can be calculated according to the Scherrer formula D = Kλ / (βcosθ), using the data obtained by XRD test, wherein λ is the X-ray wavelength, λ is 0.154056 nm, β is the half-height width of the diffraction peak, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve-fitted in Jade software, and the Jade outputs a fitting report. According to the angle 2θ value and the Peak FWHM value (diffraction peak half-height width) corresponding to each diffraction peak in the fitting report, and converting the Peak FWHM value into radians β = (FWHM / 180*3.14), the grain size of each diffraction peak is calculated by D = Kλ / (βcosθ), and then averaged to obtain the average grain size. Test method of crystal content / crystallinity: the X-ray diffraction test result file (RAW format) is imported into X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud, Topas), fitting and calculation are performed, and the crystal content / crystallinity in the glass-ceramic sample can be obtained. The ratio of the fitted crystal phase peak area to the total peak area is the crystal content, i.e. the crystallinity referred to in the present application.
[0105] b value determination: the b value of the sample is tested by using a Japanese Konica Minolta spectrophotometer CM-3600A, and the average value of 5 parallel samples is taken as the b value result of the sample to be tested.
[0106] Determination of transmittance: test according to the standard of GB / T 7962.12-2010 Colorless optical glass Test methods Part 12: Spectral transmittance. First, clean the glass-ceramic sample to be tested in an ultrasonic cleaning machine, and the cleaning conditions are as follows: cleaning time 5-10 min; cleaning agent used: commonly used washing agent diluted 10 times; cleaning temperature: 45-65 DEG C; cleaning frequency: 20-40 KHZ. Then use a haze meter (Japanese Konica Minolta spectrophotometer CM-3600A) to test its transmittance under different wavelengths of light.
[0107] The transmittance of the sample under 550 nm wavelength light is measured by using a Japanese Konica Minolta spectrophotometer CM-3600A, and the average value of 5 parallel samples is taken as the transmittance result of the sample to be tested under 550 nm wavelength light.
[0108] The thickness of the glass: determined by a micrometer test. It should be understood that in the thickness direction, the degree of ion exchange varies from the surface to the center in a gradient, and the total Na-K and / or Li-Na exchange amount is generally not more than 1% of the total mass of the sample, and the difference in ionic radius is pm level, so the expansion effect in the thickness direction is slight, and it can be approximately considered that the thickness is basically unchanged. That is, the thickness of the glass-ceramic changes very little before and after chemical strengthening, which can be ignored.
[0109] Determination of density: the density value of the glass-ceramic sample is tested according to the principle of "Archimedes drainage method", and the testing instrument used in the application is ALFA MIRAGE electronic density balance SD-200. In order to at least solve the problem in the related art that the optical and mechanical properties of the glass-ceramic cannot be effectively guaranteed by exchanging crystallinity for a relatively pure target crystal phase, an embodiment of the application provides a precursor glass suitable for low-temperature crystallization treatment, which can be understood as a raw glass based on glass raw materials, and the precursor glass satisfies the following relationship:
[0110] δ=a*n RO +b*(n Na2O +n K2O )+c*n Li2O ,
[0111] η=12.5 / (0.55+4.61*i^0.57)
[0112] 0.25≤δ / η≤0.6;
[0113] Wherein, δ represents the ion activity of each ion in the glass, η represents the correlation index of the kinetic energy of the thermal motion of the oxide molecules in the glass and the characteristic temperature point, n represents the molar percentage content of each oxide, a, b, and c are constants, and i is a characteristic temperature coefficient, 1.3
[0114] In the alternative embodiment of the embodiment, the value of δ / η can be 0.25, 0.27, 0.29, 0.31, 0.33, 0.35, 0.37, 0.39, 0.41, 0.43, 0.45, 0.47, 0.49, 0.51, 0.53, 0.55, 0.57, 0.59, 0.6, and in addition, the value range of δ / η can be 0.27-0.59, 0.29-0.57, 0.31-0.55, 0.33-0.53, 0.35-0.51, 0.37-0.49, 0.39-0.47, and 0.41-0.45.
[0115] It should be noted that i is a characteristic temperature coefficient, which corresponds to the temperature of the characteristic viscosity point of the heat treatment process involved in the embodiments of the present application. In actual applications, the glass characteristic temperature points such as the glass softening point, the strain point, the annealing point, and the glass transition temperature can be obtained by testing, calculating, and fitting through high-temperature rotary viscometers, flat plate viscometers, strain point annealing point testers, linear dilatometers, differential scanning calorimeters (DSC), and the like to obtain accurate temperatures, and then the viscosity-temperature curve can be obtained by fitting the viscosity and the temperature through the VFT equation, so that the temperature of the characteristic viscosity point can be obtained.
[0116] The applicant found through research that alkali metals and alkaline earth metals have a significant effect on increasing the glass crystallization tendency, and Na2O and K2O have a prominent effect on increasing the glass crystallization tendency. This is because their ionic radii are small, and they are more easily attracted by high-field strength ions under suitable temperature conditions. By introducing the δ calculation formula, the different effects of the oxides in the glass can be calculated and classified, and the different factors affecting the crystallization tendency can be comprehensively evaluated to describe the relationship between the electric field strength of the different oxides in the glass and the ion migration. By introducing the η calculation formula, the relationship between the kinetic energy of the molecular thermal motion of the glass oxides and the characteristic temperature point is associated with the above-mentioned crystallization strength, and the crystallization tendency at a relatively low temperature is comprehensively evaluated.
[0117] In the embodiments, the ion activity degree of the glass is described by δ / η to represent the crystallization tendency of the glass. By setting the value of δ / η within a specific range, the viscosity of the glass can be suitable for low-temperature crystallization. It is worth mentioning that the low-temperature crystallization mentioned in the embodiments refers to a crystallization temperature lower than the hot forming and hot working temperature, but still can ensure a high crystallinity. Since the crystallization temperature is relatively low, the generation of impurities can be effectively controlled.
[0118] In the optional embodiments of the present application, the precursor glass also satisfies the following relationship:
[0119] ε=A*n SiO2 +B*n B2O3 +C*n Al2O3 +D*n P2O5 +E*n RO +F*n R2O ,
[0120] 22≤ε≤24.8;
[0121] wherein, ε represents the atomic packing degree, n represents the molar percentage content of each oxide, A, B, C, D, E, and F are constants, A=26.1-28.3, B=18.3-27.3, C=40.2-42.7, D=56.1-63.7, E=12.2-22.6, and F=10.9-36.2.
[0122] In an alternative embodiment of the present embodiment, the value of ε can be 22.1, 22.3, 22.5, 22.7, 22.9, 23.1, 23.3, 23.5, 23.7, 23.9, 24.1, 24.3, 24.5, 24.7, preferably, the value of ε ranges from 22 to 24.5. In alternative embodiments, the value can also range from 22.1 to 24.7, 22.3 to 24.5, 22.5 to 24.3, 22.7 to 24.1, 22.9 to 23.9, 23.1 to 23.7, 23.3 to 23.5.
[0123] In an alternative embodiment of the present embodiment, the above atomic packing degree calculation formula can be further represented as:
[0124] ε = A*n SiO2 +B*n B2O3 +C*n Al2O3 +D*n P2O5 +12.5*n MgO +14.4*n CaO +11.2*n Li2O +20.2*n Na2O +34*n K2O ; 22.5 ≤ ε ≤ 24.1.
[0125] It should be noted that the present embodiment can improve the chemical stability and impact resistance of the glass phase in the glass-ceramics by regulating the glass component content through the atomic packing degree calculation formula.
[0126] It is worth mentioning that the aforementioned formula / relationship of the present embodiment essentially quantifies the degree of change in the composition related to the glass viscosity and crystallization tendency, and can understand the bond strength between glass cations and anions, the coordination number, and the connection degree of the glass structure network, thereby grasping the relationship between the viscosity and the glass composition, which can guide the glass crystallization temperature range and has guiding significance for judging whether the glass formula is suitable for low-temperature crystallization.
[0127] The components of the precursor glass of the present embodiment are in mole percentage, including: SiO2 greater than or equal to 60% and less than or equal to 78%; Al2O3 greater than or equal to 1.5% and less than or equal to 6.7%; Li2O greater than or equal to 16% and less than or equal to 26.8%; Na2O greater than or equal to 0 and less than or equal to 6.5%; K2O greater than or equal to 0 and less than or equal to 4%; P2O5 greater than or equal to 0.3% and less than or equal to 2.5%; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, BaO; a fining agent greater than or equal to 0 and less than or equal to 1%.
[0128] SiO2is a basic component of the glass composition provided by the present application, and is a glass and microcrystalline glass network structure former, and can form lithium silicate and lithium disilicate after crystallization. It should be noted that if the content of SiO2is low, the crystals formed in the microcrystalline glass will be less and the crystals will be easy to become coarse, affecting the haze, ball drop test height and other properties of the microcrystalline glass and microcrystalline glass products, therefore, the lower limit of the content of SiO2is set to 60%; in addition, if the content of SiO2is higher than a certain level, it will make the glass melting temperature high, the material melting difficult, and not easy to shape, affecting the consistency of the glass, therefore, the upper limit of the content of SiO2is set to 78%. In some embodiments, the glass composition can contain about 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78% of SiO2. In some embodiments, the glass composition can also contain SiO2such as the following content: greater than or equal to 61% and less than or equal to 77%, greater than or equal to 62% and less than or equal to 76%, greater than or equal to 63% and less than or equal to 75%, greater than or equal to 64% and less than or equal to 74%, greater than or equal to 65% and less than or equal to 73%, greater than or equal to 66% and less than or equal to 72%, greater than or equal to 67% and less than or equal to 71%, greater than or equal to 68% and less than or equal to 70%.
[0129] Al2O3may be a component of the glass network structure or a cation network exoskeleton for charge balance. In the present application, Al2O3enters the glass network structure entirely, increasing the ion exchange layer depth and surface compressive stress of the microcrystalline glass product, improving the chemical stability of the glass and improving the mechanical properties of the glass. On the one hand, if its content is lower than a certain level, it will lead to poor results, therefore, the lower limit of the mass percentage content of Al2O3is 1.5%; on the other hand, if the content of Al2O3is higher than a certain level, the melting and devitrification resistance of the glass will decrease, and the crystals will easily increase during crystallization, reducing the strength of the microcrystalline glass and the microcrystalline glass product, therefore, the upper limit of the content of Al2O3is 6.7%. In some embodiments, the glass composition can contain about 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 6.7% of Al2O3. In some embodiments, the glass composition can also contain Al2O3such as the following content: greater than or equal to 2% and less than or equal to 6.5%, greater than or equal to 2.5% and less than or equal to 6%, greater than or equal to 3% and less than or equal to 5.5%, greater than or equal to 3.5% and less than or equal to 5%, greater than or equal to 4% and less than or equal to 4.5%.
[0130] Li2O is an essential component that forms a crystalline phase upon crystallization, contributing to the formation of lithium-containing crystalline phases such as lithium disilicate, petalite, and lithium silicate. It is also essential for chemical strengthening. However, if its content falls below a certain level, the effect is poor. Therefore, the lower limit of the Li2O content is 16%. Furthermore, if its content exceeds a certain level, the chemical stability of the glass is negatively impacted. Therefore, the upper limit of the Li2O content is preferably 26.8%. In some embodiments, the glass composition may include approximately 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, or 26.8% Li2O. In some embodiments, the glass composition may further include Li2O in an amount such as greater than or equal to 16.5% and less than or equal to 26.5%, greater than or equal to 17% and less than or equal to 26%, greater than or equal to 17.5% and less than or equal to 25.5%, greater than or equal to 18% and less than or equal to 25%, greater than or equal to 18.5% and less than or equal to 24.5%, greater than or equal to 19% and less than or equal to 24%, greater than or equal to 19.5% and less than or equal to 23.5%, greater than or equal to 20% and less than or equal to 23%, greater than or equal to 20.5% and less than or equal to 22.5%, or greater than or equal to 21% and less than or equal to 22%.
[0131] P2O5 helps improve the low-temperature melting properties of glass, enables phase separation and formation of crystal nuclei in the glass, and improves the thermal expansion stability of the glass during the crystallization process. The lower limit of the P2O5 content can be 0.3%. However, excessive P2O5 can easily reduce the glass's resistance to devitrification and cause phase separation, and the mechanical properties of the glass tend to deteriorate. Therefore, the upper limit of the P2O5 content is 2.5%. In some embodiments, the glass composition may include approximately 0.3%, 0.5%, 1%, 1.5%, 2%, or 2.5% P2O5. In some embodiments, the glass composition may also include P2O5 in amounts such as greater than or equal to 0.5% and less than or equal to 2%, or greater than or equal to 1% and less than or equal to 1.5%.
[0132] Zr02, as a nucleating agent, also helps to improve the chemical durability of the glass. The lower limit of the Zr02content in this embodiment can be 0, and if the Zr02content is too high, the glass is prone to have a reduced resistance to devitrification, and the control of the glass crystallization process is difficult, which requires a higher crystallization temperature. Therefore, the upper limit of the Zr02content is 5%. In some embodiments, the glass composition can contain about 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% Zr02. In some embodiments, the glass composition can also contain Zr02in an amount of, for example, greater than or equal to 0.5% and less than or equal to 4.5%, greater than or equal to 1% and less than or equal to 4%, greater than or equal to 1.5% and less than or equal to 3.5%, or greater than or equal to 2% and less than or equal to 3%.
[0133] Na20 helps to reduce the glass transition temperature, the crystallization temperature, and suppress the precipitation of unintended phases, and the lower limit of the Na20 content can be 0. If the Na20 content is too high, the thermal expansion coefficient of the glass increases and the thermal stability of the glass decreases, and therefore the upper limit of the Na20 content is set to 6.5%. In some embodiments, the glass composition can contain about 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, or 6.5% Na20. In some embodiments, the glass composition can also contain Na20 in an amount of, for example, greater than or equal to 0.5% and less than or equal to 6%, greater than or equal to 1% and less than or equal to 5.5%, greater than or equal to 1.5% and less than or equal to 5%, greater than or equal to 2% and less than or equal to 4.5%, greater than or equal to 2.5% and less than or equal to 4%, or greater than or equal to 3% and less than or equal to 3.5%.
[0134] The embodiment can optionally also introduce K20 into the glass composition in a molar percentage of 0-4%, for example, 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, or 4% K20. In some embodiments, the glass composition can also contain K20 in an amount of, for example, greater than or equal to 0.5% and less than or equal to 4%, greater than or equal to 1% and less than or equal to 3.5%, greater than or equal to 1.5% and less than or equal to 3%, or greater than or equal to 2% and less than or equal to 2.5%. It is worth mentioning that when multiple alkali metal oxides are present in the glass composition, a mixed alkali effect can be achieved during the chemical strengthening process of the glass-ceramic, which can limit the migration of alkali metal ions during ion diffusion, and help to improve the chemical stability of the glass. In addition, the interaction of multiple alkali metal oxides can improve the low-temperature meltability and formability of the glass, and also has a certain effect on the reduction of the softening point temperature and the molding temperature of the glass, i.e., the difficulty of chemical strengthening of the glass-ceramic is reduced.
[0135] RO is an alkaline earth metal oxide, including at least one of CaO, MgO, ZnO, and BaO. The lower limit of the alkaline earth metal oxide content is 0 and the upper limit is 5.3%. In some embodiments, the glass composition may include approximately 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or 5.3% of the alkaline earth metal oxide. In some embodiments, the glass composition may also include alkaline earth metal oxide in an amount such as greater than or equal to 0.5% and less than or equal to 5%, greater than or equal to 1% and less than or equal to 4.5%, greater than or equal to 1.5% and less than or equal to 4%, greater than or equal to 2% and less than or equal to 3.5%, or greater than or equal to 2.5% and less than or equal to 3%.
[0136] In an optional embodiment of this embodiment, the glass composition includes: CaO (0% to 4%), MgO (0% to 4%), ZnO (0% to 4%), and BaO (0% to 4%). CaO helps reduce the high-temperature viscosity of the glass and increases its density; MgO helps reduce the viscosity of the glass, inhibits crystallization during glass forming, and improves its low-temperature melting properties; ZnO improves the melting properties of the glass, enhances its chemical stability, and refines the grain size during crystallization; and BaO improves the glass's glass-forming properties.
[0137] The glass composition of this embodiment may further include a fining agent, comprising one or more of SnO2, Sb2O3, and CeO2. The lower limit of the fining agent content is 0% and the upper limit is 1%. In some embodiments, the glass composition may include approximately 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1% of the fining agent. In some embodiments, the glass composition may further include a fining agent in an amount such as greater than or equal to 0.1% and less than or equal to 0.9%, greater than or equal to 0.2% and less than or equal to 0.8%, greater than or equal to 0.3% and less than or equal to 0.7%, or greater than or equal to 0.3% and less than or equal to 0.6%.
[0138] In an optional implementation manner of this embodiment, the components of the precursor glass, expressed in molar percentage, further include: B2O3 greater than or equal to 0 and less than or equal to 4.8%; and / or, TiO2 greater than or equal to 0% and less than or equal to 4%; and / or, Y2O3 greater than or equal to 0 and less than or equal to 4%; and / or, La2O3 greater than or equal to 0 and less than or equal to 0.5%.
[0139] B2O3 can reduce the melting temperature of the glass, while remaining in the glass phase after crystallization, ensuring the structural stability of the glass phase and improving the chemical stability of the glass-ceramic. However, too high a content of B2O3 can increase the volatility during the glass melting process and increase the difficulty of glass homogenization. Based on this, the upper limit of the content of B2O3 is set to 4.8%. In some embodiments, the glass composition can contain about 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 4.8% of B2O3. In some embodiments, the glass composition can also contain B2O3 in an amount such as: greater than or equal to 0.5% and less than or equal to 4.8%, greater than or equal to 1% and less than or equal to 4.5%, greater than or equal to 1.5% and less than or equal to 4%, greater than or equal to 2% and less than or equal to 3.5%, greater than or equal to 2.5% and less than or equal to 3%.
[0140] TiO2 helps to reduce the melting temperature of the glass and improve the chemical stability. By introducing TiO2 in an amount of less than 4%, the glass crystallization process can be easily controlled. The present embodiment optionally contains about 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% of TiO2. In some embodiments, the glass composition can also contain TiO2 in an amount such as: greater than or equal to 0.5% and less than or equal to 3.5%, greater than or equal to 1% and less than or equal to 3%, greater than or equal to 1.5% and less than or equal to 2.5%.
[0141] An appropriate amount of Y2O3 can improve the density of the glass phase and improve the overall strength of the glass-ceramic. However, if the content of Y2O3 is too high, it will be difficult to obtain a larger compressive stress value during the chemical strengthening process of the glass-ceramic. The present embodiment optionally contains about 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% of Y2O3. In some embodiments, the glass composition can also contain Y2O3 in an amount such as: greater than or equal to 0.5% and less than or equal to 3.5%, greater than or equal to 1% and less than or equal to 3%, greater than or equal to 1.5% and less than or equal to 2.5%.
[0142] In some embodiments, La2O3, Y2O3 has high field strength, has an accumulation effect, can strongly attract surrounding non-bridging oxygen (NBO, i.e. broken Si-O- bond), making the glass structure more dense, while forming La-O, Y-O bonds with higher bond strength, improving the chemical stability of the glass; La2O3, Y2O3 is also an oxide commonly used in optical glass, which can reduce dispersion and improve the optical performance of the glass. The present embodiment optionally contains about 0, 0.1%, 0.15%, 0.25%, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% of La2O3 and / or Y2O3. In some embodiments, the glass composition can also contain La2O3 and / or Y2O3 in an amount of, for example, greater than or equal to 0% and less than or equal to 4%, greater than or equal to 0.1% and less than or equal to 3%, greater than or equal to 0.15% and less than or equal to 0.3%.
[0143] Nb2O5, Ta2O5 has high field strength, which can improve chemical stability, reduce glass dispersion and improve optical performance; among them, Ta2O5 has lower dispersion and higher Abbe number, and has very strong corrosion resistance, which can significantly improve the chemical stability; Nb2O5 also has the effects of fluxing, increasing glass hardness and scratch resistance. The present embodiment optionally contains about 0, 0.1%, 0.15%, 0.25%, 0.3%, 0.5%, 1% of Nb2O5 and / or Ta2O5. In some embodiments, the glass composition can also contain Nb2O5 and / or Ta2O5 in an amount of, for example, greater than or equal to 0% and less than or equal to 1%, greater than or equal to 0.15% and less than or equal to 0.5%, greater than or equal to 0.2% and less than or equal to 0.3%.
[0144] HfO2 has high field strength and can improve chemical stability, and has strong absorption of ultraviolet wavelength, which can improve the radiation resistance and has obvious effect on protecting human eye health. The present embodiment optionally contains about 0, 0.1%, 0.15%, 0.25%, 0.3%, 0.5%, 1% of HfO2. In some embodiments, the glass composition can also contain HfO2 in an amount of, for example, greater than or equal to 0% and less than or equal to 1%, greater than or equal to 0.15% and less than or equal to 0.5%, greater than or equal to 0.2% and less than or equal to 0.3%.
[0145] Bi2O3 has a very high refractive index, low dispersion properties, and a low melting point that can reduce the glass crystallization temperature. In some embodiments, the glass composition can further include Bi2O3 in an amount of greater than or equal to 0% and less than or equal to 1%, greater than or equal to 0.15% and less than or equal to 0.5%, or greater than or equal to 0.2% and less than or equal to 0.3%.
[0146] In optional embodiments of the present embodiments, the components of the precursor glass are in mole percent and satisfy at least one of the following relationships:
[0147] 5≤n Li2O / (n Na2O +n K2O )≤21;
[0148] 3≤n Li2O / (n CaO +n MgO +n ZnO )≤25;
[0149] 0.2≤n Li2O / (n SiO2 +n Al2O3 )≤0.39.
[0150] Li2O, Na2O, and K2O are alkali metal oxides. By adding alkali metal oxides, a mixed alkali effect can be formed to improve the glass network cross-linking density, chemical stability, and other properties, and the product stability is obviously improved. Li2O / (Na2O+K2O) needs to satisfy a certain value range. If the ratio of (Na2O+K2O) is too low, the mixed alkali effect cannot be formed, and if the ratio of (Na2O+K2O) is too high, the formation ratio and speed of lithium-containing crystals in the glass will be affected. (CaO+MgO+ZnO) has a high field strength, which can enhance the mechanical properties of the glass, such as elastic modulus and Vickers hardness. If the ratio of (CaO+MgO+ZnO) is too low, the beneficial effect of enhancing the mechanical properties cannot be achieved, and if the ratio is too high, the crystal will grow abnormally, and it is difficult to form microcrystals. (SiO2+Al2O3) is the main network former in the glass, which plays a decisive role in the glass viscosity and network cross-linking density. If the ratio of (SiO2+Al2O3) is too low, it is difficult to form controllable crystallization under suitable viscosity temperature conditions, and if the ratio is too high, the glass crystallinity and crystal size will be affected, and the glass viscosity will be too high, which is not conducive to production.
[0151] Next, the embodiments of the present application also provide a microcrystalline glass, which is obtained after the aforementioned precursor glass is heat treated (i.e. nucleation and crystallization treatment), and has a lower limit of crystallization temperature of 553-639 ℃ and an upper limit of crystallization temperature of 989-1123 ℃. The microcrystalline glass satisfies at least one of the following performance indicators: Vickers hardness is greater than or equal to 727 kgf / mm 2 , fracture toughness is greater than or equal to 1.03 Mpa·m 1 / 2 , Young's modulus is greater than or equal to 78.3 GPa, shear modulus is greater than or equal to 33.27 GPa, |B| value is less than or equal to 0.77% when the thickness is 0.55 mm, haze is less than or equal to 0.15%, and the transmittance of visible light with a wavelength of 550 nm is greater than or equal to 91%.
[0152] The embodiments of the present application exemplarily provide a first microcrystalline glass, the components of which are expressed in mole percentage, including: greater than or equal to 60% and less than or equal to 78% of SiO2; greater than or equal to 2% and less than or equal to 6.7% of Al2O3; greater than or equal to 16% and less than or equal to 24% of Li2O; greater than or equal to 0 and less than or equal to 2.2% of P2O5; greater than or equal to 0 and less than or equal to 5% of ZrO2; greater than or equal to 0 and less than or equal to 5.3% of RO, and RO includes at least one of CaO, MgO, ZnO, BaO; greater than or equal to 0% and less than or equal to 5% of Na2O; greater than or equal to 0 and less than or equal to 4% of K2O; greater than or equal to 0 and less than or equal to 1% of a clarifying agent.
[0153] wherein the preferred content of SiO2is 66-71.28%, more preferably 66.5-70.8%, further preferably 67.1-69.5%; the preferred content of Al2O3is 3-5.5%, more preferably 3.5-5.2%, further preferably 3.5-4.6%; the preferred content of P2O5is 0.3-1.6%, more preferably 0.6-1.2%, further preferably 0.8-1.1%; the preferred content of ZrO2is 0-3.7%, more preferably 0-2.6%, further preferably 0.6-2.6%; the preferred content of Na2O is 0-3.5%, more preferably 0-2.0%, further preferably 0-1.5%; the preferred content of K2O is 0-2%, more preferably 0-0.5%, further preferably 0-0.3%; the preferred content of Li2O is 18-23.5%, more preferably 20.5-23.5%, further preferably 21.5-23.5%. For the above alkaline earth metal oxides, the glass-ceramic comprises: CaO greater than or equal to 0 and less than or equal to 4%, MgO greater than or equal to 0 and less than or equal to 4%, ZnO greater than or equal to 0 and less than or equal to 4%, BaO greater than or equal to 0 and less than or equal to 4%, wherein the preferred content of CaO is 0-2.5%, more preferably 0-1.5%, further preferably 0.2-0.5%, the preferred content of MgO is 0-2.5%, more preferably 0-1%, further preferably 0-0.5%. For the above fining agent, it is preferably SnO2, and the preferred content of SnO2is 0.05-0.5%, more preferably 0.05-0.2%, further preferably 0.05-0.15%. In addition, the glass-ceramic can further comprise: B2O3 greater than or equal to 0 and less than or equal to 4.8%, and / or, TiO2 greater than or equal to 0% and less than or equal to 4%, and / or, Y2O3 greater than or equal to 0 and less than or equal to 4%, and / or, La2O3 greater than or equal to 0 and less than or equal to 0.5%, wherein the preferred content of B2O3 is 0-3%, more preferably 0-1.6%, further preferably 0-0.4%, the preferred content of TiO2 is 0-2.6%, more preferably 0-1.2%, further preferably 0-0.6%, the preferred content of Y2O3 is 0-2%, more preferably 0-0.5%, further preferably 0-0.3%, the preferred content of La2O3 is 0-2%, more preferably 0-0.5%, further preferably 0-0.3%.
[0154] The crystalline phase of the microcrystalline glass is lithium disilicate and petalite, the average grain size of the lithium disilicate crystalline phase is less than or equal to 32.5-39.3 nm, the average grain size of the petalite crystalline phase is less than or equal to 24.6-29.1 nm, and the crystallinity is greater than or equal to 84.72%. Further, the lithium disilicate crystalline phase satisfies the following indexes: the size of the grains accounting for 98% of the whole lithium disilicate crystalline phase is less than or equal to 55 nm, the size of the grains accounting for 95% of the whole lithium disilicate crystalline phase is less than or equal to 50 nm, and the size of the grains accounting for 80% of the whole lithium disilicate crystalline phase is less than or equal to 45 nm; the petalite crystalline phase satisfies the following indexes: the size of the grains accounting for 98% of the whole petalite crystalline phase is less than or equal to 45 nm, the size of the grains accounting for 95% of the whole petalite crystalline phase is less than or equal to 40 nm, and the size of the grains accounting for 80% of the whole petalite crystalline phase is less than or equal to 30 nm; and the crystallinity is greater than or equal to 85.8%.
[0155] The second microcrystalline glass provided in the embodiments of the present application comprises, in terms of mole percentage, the following components: SiO2 is greater than or equal to 60% and less than or equal to 78%; Al2O3 is greater than or equal to 1.5% and less than or equal to 5.5%; Li2O is greater than or equal to 18% and less than or equal to 26.8%; P2O5 is greater than or equal to 0.1 and less than or equal to 2.5%; ZrO2 is greater than or equal to 0 and less than or equal to 5%; RO is greater than or equal to 0 and less than or equal to 3.4%, and RO comprises at least one of CaO, MgO, ZnO and BaO; Na2O is greater than or equal to 0 and less than or equal to 6.5%; K2O is greater than or equal to 0 and less than or equal to 4%; and a refining agent is greater than or equal to 0 and less than or equal to 1%.
[0156] wherein the preferred content of SiO2is 61.7-75.4%, more preferably 62.4-71.3%, and further preferably 64.7-68.3%; the preferred content of Al2O3is 2-5.5%, more preferably 2-4.2%, and further preferably 2.5-3.5%; the preferred content of P2O5is 0.6-2.5%, more preferably 0.6-1.5%, and further preferably 1.0-1.4%; the preferred content of ZrO2is 0-3.7%, more preferably 0-2.6%, and further preferably 0.6-2.6%; the preferred content of Na2O is 0-4.8%, more preferably 0-3.1%, and further preferably 1.0-3.1%; the preferred content of K2O is 0-2%, more preferably 0-1.2%, and further preferably 0-0.6%; and the preferred content of Li2O is 18-25.8%, more preferably 22.2-25.8%, and further preferably 23.4-24.4%. For the above alkaline earth metal oxides, the glass-ceramic includes greater than or equal to 0 and less than or equal to 4% CaO, greater than or equal to 0 and less than or equal to 4% MgO, greater than or equal to 0 and less than or equal to 4% ZnO, and greater than or equal to 0 and less than or equal to 4% BaO, wherein the preferred content of CaO is 0-2.5%, more preferably 0-1.5%, and further preferably 0-0.5%, and the preferred content of MgO is 0-2.5%, more preferably 0-1.5%, and further preferably 0-0.5%. For the above fining agent, the preferred fining agent is SnO2, and the preferred content of SnO2is 0.05-0.5%, more preferably 0.05-0.2%, and further preferably 0.05-0.15%. Additionally, the glass-ceramic can include greater than or equal to 0 and less than or equal to 4.8% B2O3, and / or, greater than or equal to 0% and less than or equal to 4% TiO2, and / or, greater than or equal to 0 and less than or equal to 4% Y2O3, and / or, greater than or equal to 0 and less than or equal to 0.5% La2O3, wherein the preferred content of B2O3is 0-3%, more preferably 0-1.6%, and further preferably 0-0.4%, the preferred content of TiO2is 0-2.6%, more preferably 0-1.2%, and further preferably 0-0.6%, the preferred content of Y2O3is 0-2%, more preferably 0-0.5%, and further preferably 0-0.3%, and the preferred content of La2O3is 0-2%, more preferably 0-0.5%, and further preferably 0-0.3%.
[0157] The crystalline phase of the glass-ceramics is lithium disilicate, and the lithium disilicate crystalline phase satisfies the following indexes: the average grain size is less than or equal to 38-45.7 nm, and the crystallinity is greater than or equal to 56.38%. Further, the lithium disilicate crystalline phase satisfies the following indexes: the size of the grains accounting for 98% of the whole crystalline phase is less than or equal to 60 nm, the size of the grains accounting for 95% of the whole crystalline phase is less than or equal to 55 nm, and the size of the grains accounting for 80% of the whole crystalline phase is less than or equal to 50 nm; and the crystallinity is greater than or equal to 61.22%.
[0158] Next, the embodiment of the present application also provides a chemically strengthened glass-ceramics, which is obtained by sequentially subjecting the precursor glass provided in the foregoing embodiment to heat treatment and ion exchange treatment.
[0159] It is worth mentioning that the chemically strengthened glass-ceramics of the embodiment satisfies at least one of the following performance indexes: the Vickers hardness is greater than or equal to 655 kgf / mm 2 , the fracture toughness is greater than or equal to 1.2 Mpa·m 1 / 2 , the Young's modulus is greater than or equal to 98.38 GPa, the shear modulus is greater than or equal to 39.35 GPa, the |B| value when the thickness is 0.55 mm is less than or equal to 0.77%, the haze is less than or equal to 0.13%, the transmittance relative to visible light with a wavelength of 550 nm is greater than or equal to 91%, the nine-point ball drop test height based on a 32 g steel ball when the thickness is 0.55 mm is 980-1290 mm, the maximum bending strength is 1052-1200 MPa, the whole machine drop test height based on 80 mesh sandpaper is 850-1020 mm, and the whole machine drop test height based on 180 mesh sandpaper is 1200-1600 mm.
[0160] Correspondingly, the embodiment of the present application also provides a glass preparation method, which specifically comprises:
[0161] Step A: uniformly mixing raw materials according to a glass formula, melting at a preset melting temperature and for a preset melting time, and obtaining a precursor glass after forming and annealing;
[0162] Step B: subjecting the precursor glass to heat treatment to obtain a glass-ceramics.
[0163] The precursor glass satisfies the following relationship:
[0164] δ=a*n RO +b*(n Na2O +n K2O )+c*n Li2O ,
[0165] η=12.5 / (0.55+4.61*i^0.57),
[0166] 0.25≤δ / η≤0.6;
[0167] wherein, δ represents the ion activity of each ion in the glass, η represents the correlation index of the kinetic energy of the thermal motion of the oxide molecules in the glass and the characteristic temperature point, n represents the corresponding molar percentage content of each oxide, a, b, and c are constants, i is a characteristic temperature coefficient, 1.3 < A < 1.9, 1.3 < B < 2.3, 1.2 < C < 1.8, and 5.96 < i < 10.13.
[0168] In actual application, the glass raw materials are prepared according to the glass components and contents provided in the foregoing embodiments, and after the glass raw materials are mixed uniformly, the glass raw materials are melted at 1350-1550°C, and then subjected to fining, homogenizing, forming, and annealing to obtain a precursor glass. Then, the precursor glass is subjected to crystallization treatment by using a two-stage heat treatment method, the first heat treatment is nucleation treatment, the second heat treatment is crystallization treatment, and then cooled to room temperature to obtain a glass-ceramic with a desired crystallinity, grain size, and crystal phase ratio.
[0169] wherein, for the first glass-ceramic provided in the foregoing embodiments, the heat treatment process can include: placing the glass raw materials in a crystallization furnace, heating to 500-610°C at a heating rate of greater than or equal to 6°C / min and then holding for 200-300 min, then heating to 655-800°C at a heating rate of greater than or equal to 6°C / min and then holding for 60-120 min, and finally cooling at a cooling rate of less than or equal to 2°C / min.
[0170] For the second glass-ceramic provided in the foregoing embodiments, the heat treatment process can include: placing the glass raw materials in a crystallization furnace, heating to 560-590°C at a heating rate of 8-12°C / min and then holding for 220-250 min, then heating to 750-790°C at a heating rate of 8-12°C / min and then holding for 70-90 min, and finally cooling at a cooling rate of less than or equal to 2°C / min.
[0171] Thus, by using different heat treatment processes for glass raw materials with different components, glass-ceramics with desired crystal phases, crystal proportions, and grain size distributions can be obtained.
[0172] It is worth mentioning that the glass-ceramic obtained in step B can be further subjected to cold working treatment, i.e., subjected to processes such as shaping, multi-wire cutting, CNC, grinding, rough grinding, fine polishing, cleaning, etc., to obtain a glass-ceramic with a thickness of 0.35-0.7 mm.
[0173] In addition, corresponding to the second glass-ceramic provided in the foregoing embodiment, the glass-ceramic can also be subjected to heat bending treatment, wherein the pressure of the heat bending station is 0.7-1.1 MPa, and the running time of a single station is 70-110 s.
[0174] In an alternative embodiment of the present embodiment, the heat bending treatment needs to pass through four preheating stations, three hot pressing stations and two cooling stations; wherein the running temperature of the first preheating station is 430-470℃, the running temperature of the second preheating station is 530-570℃, the running temperature of the third preheating station is 630-670℃, the running temperature of the fourth preheating station is 710-730℃, the running temperature of the first hot pressing station is 740-760℃, the running temperature of the second hot pressing station is 740-760℃, the running temperature of the third hot pressing station is 580-620℃, the running temperature of the first cooling station is 430-470℃, and the running temperature of the second cooling station is 280-320℃.
[0175] In an alternative embodiment of the present embodiment, the above glass preparation method further comprises: step C, immersing the glass-ceramic into a chemical strengthening salt bath for ion exchange treatment to obtain a chemically strengthened glass-ceramic.
[0176] In the present embodiment, when the glass-ceramic is chemically strengthened, the chemical strengthening salt bath comprises, in mass percentage: greater than or equal to 9.99% and less than or equal to 39.99% KNO3, greater than or equal to 59.99% and less than or equal to 89.99% NaNO3, greater than or equal to 0.03% and less than or equal to 0.1% LiNO3, the temperature of the chemical strengthening salt bath is 460-490℃, and the ion exchange treatment time is 4-10 hours.
[0177] Chemical strengthening refers to placing the glass-ceramic in a salt bath for ion exchange treatment, so that the glass-ceramic forms a compressive stress layer and a tensile stress layer. The salt bath of the present embodiment is a mixed salt bath. Compared with the traditional multiple strengthening, the present embodiment can complete multiple ion exchange behaviors between the salt bath and the glass-ceramic at the same time through a one-time strengthening process, thereby improving the chemical strengthening efficiency and reducing the amount of salt bath used. After chemical strengthening treatment, the finally obtained chemically strengthened glass-ceramic has a deeper compressive stress layer depth and a higher surface compressive stress.
[0178] It is worth mentioning that, for the chemically strengthened glass-ceramic, after being taken out of the salt bath, the surface residual substances can be cleaned first, and then a regrinding process is performed using a flat grinder. The related parameters of the regrinding process are set as follows: the grinding skin is white grinding skin, the hardness is 75, the rotating speed of the upper grinding disc and the lower grinding disc is both 10 rpm, and the grinding powder concentration is 1.13 g / cm 3, the pressure is 150-250 kg, and the number of grinding circles is 100-300. Finally, the chemically strengthened glass can be cleaned by using a neutral cleaning agent with a pH of 7-9, thereby obtaining the chemically strengthened glass product.
[0179] Corresponding to the first glass provided in the foregoing embodiment, the chemically strengthened glass obtained after ion exchange treatment satisfies the following performance indexes: the surface compressive stress value is 255-280 MPa, the compressive stress value at a depth of 50 μm from the surface is 105-112 MPa, the compressive stress value at a depth of 80 μm from the surface is 65-70 MPa, the depth of the compressive stress layer is 121-135 μm, the absolute value of the maximum tensile stress is 100-110 MPa, and the absolute value of the average tensile stress is 59-63 MPa.
[0180] Corresponding to the second glass provided in the foregoing embodiment, the chemically strengthened glass obtained after ion exchange treatment satisfies the following performance indexes: the surface compressive stress value is 240-276 MPa, the compressive stress value at a depth of 50 μm from the surface is 102-125 MPa, the compressive stress value at a depth of 80 μm from the surface is 65-75 MPa, the depth of the compressive stress layer is 113-130 μm, the absolute value of the maximum tensile stress is 105-108 MPa, and the absolute value of the average tensile stress is 58-63 MPa.
[0181] Next, in order to explain the technical effects of the precursor glass, the glass-ceramic and the chemically strengthened glass-ceramic suitable for low-temperature crystallization of the present embodiment, the present application tests the glass products with different component contents to determine their properties. The relevant test conditions and test data of the glass products with different component contents of the present application are shown in Tables 1 and 2.
[0182] Table 1
[0183]
[0184]
[0185]
[0186]
[0187]
[0188] Table 2
[0189]
[0190]
[0191]
[0192]
[0193] On one hand, from Table 1 and Table 2, it can be seen that the nucleation temperature and crystallization temperature of the glass-ceramics of the embodiments of the present application are in a relatively low range, that is, the heat treatment process for the precursor glass is relatively mild, and the present application can ensure that the glass-ceramics can achieve sufficient crystallization degree at a low temperature stage by controlling the glass viscosity. On the other hand, referring to the mechanical property data (i.e. Vickers hardness, fracture toughness, Young's modulus, shear modulus, Poisson's ratio) and optical property data (i.e. refractive index, |B| value, haze, transmittance) provided by the embodiments in the above-mentioned Table 1 and Table 2, it can be known that even if a relatively mild heat treatment process is used in the preparation of the glass-ceramics in order to control the impurities, the finally prepared glass-ceramics can still have high crystallinity and can maintain relatively excellent mechanical properties and optical properties. That is, the present application creatively optimizes the glass component ratio from the ion activity degree in the glass, the correlation between the thermal motion energy of oxide molecules in the glass and the characteristic temperature, and the atomic packing degree, so that the glass viscosity is controlled, and a strong crystallization tendency is shown at a low temperature stage, effectively overcoming the problem that the impurity control and the mechanical properties and optical properties cannot be considered at the same time in the current glass-ceramic production process.
[0194] As shown in Figure 1 , it is a DSC test curve diagram corresponding to the glass-ceramics of Example 4, and in the DSC test spectrum of the corresponding prepared glass-ceramics, the temperature of the first endothermic peak is 531.4℃, and the temperature of the first exothermic peak is 680℃. As shown in Figure 2 , it is an XRD test curve diagram corresponding to the glass-ceramics of Example 4, from which it can be seen that the glass-ceramics provided by the present application have lithium disilicate and petalite crystal phases. As shown in Figure 3 , it is a scanning electron microscope diagram corresponding to the glass-ceramics of Example 4, from which it can be seen that the grain size of the lithium disilicate crystal phase provided by the present application is less than 50nm, and the grain size of the petalite crystal phase is less than 35nm; As shown in Figure 4 , it is a viscosity-temperature characteristic diagram corresponding to the glass-ceramics of Example 4, which is used to characterize the viscosity-temperature characteristics of the product.
[0195] It is also worth mentioning that due to the superior performance of the chemically strengthened glass-ceramics provided by the embodiments of the present application, it can be widely used for making protective cover plates of electronic devices, optical elements, photovoltaic devices or windows of household appliances, etc.
[0196] Finally, it should be noted that in the above embodiments, the description of each embodiment has its own emphasis, and the parts not described in detail in a certain embodiment can be referred to the related description of other embodiments.
[0197] The above is the description of the precursor glass, microcrystalline glass, chemically strengthened microcrystalline glass and glass preparation method provided in the application. For those skilled in the art, equivalent substitutions made in specific implementation manners and application ranges according to the idea of the embodiments of the application should be covered in the scope of claims of the application. In conclusion, the content of the specification should not be understood as a limitation on the schemes of the application.
Claims
1. A precursor glass suitable for low temperature crystallization treatment, characterized in that: The precursor glass satisfies the following relationship: δ=a*n RO +b*(n Na2O +n K2O )+c*n Li2O , η=12.5 / (0.55+4.61*i^0.57), 0.25≤δ / η≤0.6; Among them, δ represents the ionic activity of each ion in the glass, η represents the correlation index between the kinetic energy of thermal motion of oxide molecules in the glass and the characteristic temperature point, n represents the molar percentage content of each oxide, a, b, c are constants, and i is the characteristic temperature coefficient, 1.3<a<1.9, 1.3<b<2.3, 1.2<c<1.8, 5.96<i<10.
13.
2. The precursor glass according to claim 1, characterized in that The precursor glass also satisfies the following relationship: ε=A*n SiO2 +B*n B2O3 +C*n Al2O3 +D*n P2O5 +E*n RO +F*n R2O , 22≤ε≤24.8; Among them, ε represents the degree of atomic stacking, n represents the molar percentage content of each oxide, A, B, C, D, E, and F are constants, A = 26.1 to 28.3, B = 18.3 to 27.3, C = 40.2 to 42.7, D = 56.1 to 63.7, E = 12.2 to 22.6, and F = 10.9 to 36.
2.
3. The precursor glass according to claim 2, characterized in that The precursor glass also satisfies the following relationship: ε=A*n SiO2 +B*n B2O3 +C*n Al2O3 +D*n P2O5 +12.5*n MgO +14.4*n CaO +11.2*n Li2O +20.2*n Na2O +34*n K2O 4 22.5≤ε≤24.
1.
4. The precursor glass according to claim 1, characterized in that Its components, expressed in mole percentage, include: SiO2 greater than or equal to 60% and less than or equal to 78%; 1.5% or more and 6.7% or less of Al2O3; 16% or more and 26.8% or less of Li2O; greater than or equal to 0 and less than or equal to 6.5% Na2O; K2O greater than or equal to 0 and less than or equal to 4%; 0.3% or more and 2.5% or less of P2O5; ZrO2 greater than or equal to 0 and less than or equal to 5%; RO is greater than or equal to 0 and less than or equal to 5.3%, and RO includes at least one of CaO, MgO, ZnO, and BaO; Greater than or equal to 0 and less than or equal to 1% of clarifier.
5. The precursor glass according to claim 4, characterized in that Its components, measured in molar percentage, also include: greater than or equal to 0 and less than or equal to 4.8% B2O3; and / or, greater than or equal to 0% and less than or equal to 4% TiO2; and / or, greater than or equal to 0 and less than or equal to 4% Y2O3; and / or, greater than or equal to 0 and less than or equal to 0.5% La2O3.
6. The precursor glass according to claim 4, characterized in that The components thereof include, by mole percentage, greater than or equal to 1.5% and less than or equal to 5.5% of Al2O3; or greater than or equal to 2% and less than or equal to 6.7% of Al2O3.
7. The precursor glass according to claim 4, characterized in that: The components thereof include, by mole percentage, greater than or equal to 2% and less than or equal to 4.2% of Al2O3; or greater than or equal to 3.5% and less than or equal to 5.2% of Al2O3.
8. The precursor glass according to claim 4, characterized in that The components thereof include, by mole percentage, greater than or equal to 0.6% and less than or equal to 2.2% of P2O5.
9. The precursor glass according to claim 4, characterized in that: The components thereof include, by mole percentage, greater than or equal to 18% and less than or equal to 26.8% of Li2O, greater than or equal to 0 and less than or equal to 6.5% of Na2O, and greater than or equal to 0 and less than or equal to 4% of K2O.
10. The precursor glass according to claim 9, characterized in that: The components thereof include, by mole percentage, greater than or equal to 22.2% and less than or equal to 25.8% of Li2O, greater than or equal to 0 and less than or equal to 3.1% of Na2O, and greater than or equal to 0 and less than or equal to 1.2% of K2O.
11. The precursor glass according to claim 4, characterized in that: The components thereof include, by mole percentage, greater than or equal to 16% and less than or equal to 24% of Li2O, greater than or equal to 0 and less than or equal to 5% of Na2O, and greater than or equal to 0 and less than or equal to 4% of K2O.
12. The precursor glass according to claim 11, characterized in that: The components thereof include, by mole percentage, greater than or equal to 20.5% and less than or equal to 23.5% of Li2O, greater than or equal to 0 and less than or equal to 2% of Na2O, and greater than or equal to 0 and less than or equal to 0.5% of K2O.
13. The precursor glass according to claim 3, characterized in that: Its components also include at least one of Nb2O5, Ta2O5, HfO2, and Bi2O3.
14. The precursor glass according to claim 4, characterized in that: The components of the precursor glass are expressed in mole percentages and satisfy at least one of the following relationships: 5≤n Li2O / (n Na2O +n K2O )≤21; 3≤n Li2O / (n CaO +n MgO +n ZnO )≤25; 0.2≤n Li2O / (n SiO2 +n Al2O3 )≤0.39。 15. A glass-ceramic, characterized in that: The glass-ceramics is obtained by heat treating the precursor glass according to any one of claims 1 to 13.
16. The glass-ceramic according to claim 15, characterized in that: The lower limit of crystallization temperature is 553~639℃, and the upper limit of crystallization temperature is 989~1123℃.
17. The glass-ceramics according to claim 15, characterized in that The crystalline phase includes lithium disilicate and petalite, the average grain size of the lithium disilicate is less than or equal to 32.5-39.3 nm, the average grain size of the petalite is less than or equal to 24.6-29.1 nm, and the crystallinity is greater than or equal to 84.72%.
18. The glass-ceramics according to claim 17, characterized in that: The lithium disilicate crystalline phase meets the following indicators: 98% of the grains in the lithium disilicate crystalline phase have a size of less than or equal to 55 nm, 95% of the grains in the lithium disilicate crystalline phase have a size of less than or equal to 50 nm, and 80% of the grains in the lithium disilicate crystalline phase have a size of less than or equal to 45 nm. The petalite crystalline phase meets the following indicators: 98% of the grains in the petalite crystalline phase are less than or equal to 45 nm in size, 95% of the grains in the petalite crystalline phase are less than or equal to 40 nm in size, and 80% of the grains in the petalite crystalline phase are less than or equal to 30 nm in size; The crystallinity is greater than or equal to 85.8%.
19. The glass-ceramic according to any one of claims 15 to 18, characterized in that Meet at least one of the following performance indicators: Vickers hardness greater than or equal to 727kgf / mm 2 , fracture toughness greater than or equal to 1.03Mpa·m 1 / 2 , Young's modulus greater than or equal to 78.3GPa, shear modulus greater than or equal to 33.27GPa, |B| value less than or equal to 0.77% when the thickness is 0.55mm, haze less than or equal to 0.15%, and transmittance relative to visible light with a wavelength of 550nm greater than or equal to 91%.
20. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened glass-ceramics is obtained by sequentially subjecting the precursor glass according to any one of claims 1 to 14 to heat treatment and ion exchange treatment.
21. The chemically strengthened glass-ceramics according to claim 18, wherein Meet at least one of the following performance indicators: Vickers hardness greater than or equal to 655kgf / mm 2 , fracture toughness greater than or equal to 1.2Mpa·m 1 / 2 , Young's modulus greater than or equal to 98.38 GPa, shear modulus greater than or equal to 39.35 GPa, |B| value less than or equal to 0.77% when the thickness is 0.55 mm, haze less than or equal to 0.13%, transmittance relative to visible light with a wavelength of 550 nm is greater than or equal to 91%, the nine-point drop test height based on a 32g steel ball when the thickness is 0.55 mm is 980~1290 mm, the maximum bending strength is 1052~1200 MPa, the whole machine drop test height based on 80 mesh sandpaper is 850~1020 mm, and the whole machine drop test height based on 180 mesh sandpaper is 1200~1600 mm.
22. A method for preparing glass, characterized in that: include: The raw materials are mixed evenly according to the glass formula, melted at a preset melting temperature and melting time, and then formed and annealed to obtain a precursor glass; heat-treating the precursor glass to obtain glass-ceramics; Wherein, the precursor glass satisfies the following relationship: δ=a*n RO +b*(n Na2O +n K2O )+c*n Li2O , η=12.5 / (0.55+4.61*i^0.57), 0.21≤δ / η≤0.89; Here, δ represents the ionic activity of each ion in the glass, η represents the correlation between the kinetic energy of thermal motion of oxide molecules in the glass and the characteristic temperature point, n represents the molar percentage of each oxide, and I is the characteristic temperature coefficient, which is specifically stated in the specification as 1.3 < a < 1.9, 1.3 < b < 2.3, 1.2 < c < 1.8, and 5.96 < i < 10.
13.
23. The glass preparation method according to claim 22, characterized in that: The heat treatment of the precursor glass comprises: The precursor glass is placed in a crystallization furnace, heated to 500-610°C at a heating rate greater than or equal to 6°C / min, and then kept warm for 200-300 minutes, then heated to 655-800°C at a heating rate greater than or equal to 6°C / min, and then kept warm for 60-120 minutes, and finally cooled at a cooling rate less than or equal to 2°C / min.
24. The glass preparation method according to claim 22, characterized in that: The crystallization heat treatment of the precursor glass comprises: The precursor glass is placed in a crystallization furnace, heated to 560-590°C at a heating rate of 8-12°C / min, and then kept warm for 220-250 minutes. Then, it is heated to 750-790°C at a heating rate of 8-12°C / min, and then kept warm for 70-90 minutes. Finally, it is cooled at a cooling rate of less than or equal to 2°C / min.
25. The glass preparation method according to claim 22, characterized in that: Also includes: The glass-ceramics is subjected to heat bending treatment at a heat bending workstation; wherein the pressure of the heat bending workstation is 0.7 to 1.1 MPa, and the operation time of a single workstation is 70 to 110 seconds.
26. The glass preparation method according to claim 25, characterized in that: The hot bending process needs to go through four preheating workstations, three hot pressing workstations and two cooling workstations; Among them, the operating temperature of the first preheating workstation is 430~470℃, the operating temperature of the second preheating workstation is 530~570℃, the operating temperature of the third preheating workstation is 630~670℃, the operating temperature of the fourth preheating workstation is 710~730℃, the operating temperature of the first hot pressing workstation is 740~760℃, the operating temperature of the second hot pressing workstation is 740~760℃, the operating temperature of the third hot pressing workstation is 580~620℃, the operating temperature of the first cooling workstation is 430~470℃, and the operating temperature of the second cooling workstation is 280~320℃.
27. The glass preparation method according to claim 22, characterized in that: Also includes: immersing the glass-ceramics in a chemically strengthened salt bath for ion exchange treatment to obtain chemically strengthened glass-ceramics; The chemical strengthening salt bath comprises, by mass percentage, KNO3 greater than or equal to 9.99% and less than or equal to 39.99%, NaNO3 greater than or equal to 59.99 and less than or equal to 89.99%, and LiNO3 greater than or equal to 0.03% and less than or equal to 0.1%.
28. The glass preparation method according to claim 27, characterized in that: The temperature of the chemical strengthening salt bath is 460-490° C., and the duration of the ion exchange treatment is 4-10 hours.
Citation Information
Patent Citations
Black microcrystalline glass as well as preparation method and application thereof
CN114772935A
3D microcrystalline glass, preparation method thereof and pre-crystallized microcrystalline glass
CN115872622A
Glass for chemical strengthening, chemically strengthened glass, electronic device, and method for producing chemically strengthened glass
CN118878204A
Preparation method of microcrystalline glass, chemically strengthened microcrystalline glass and microcrystalline glass product
CN119143397A
3D microcrystalline glass, preparation method therefor, and pre-crystallized microcrystalline glass
WO2024109495A1